South Borneo as an ancient Sprachbund area - Adelaar, Alexander (Wacana, Journal of the Humanities of Indonesia, 2021)
In South and Central Kalimantan (southern Borneo) there are some unusual linguistic features shared among languages which are adjacent but do not belong to the same genetic linguistic subgroups. These languages are predominantly Banjar Malay (a Malayic language), Ngaju (a West Barito language), and Ma’anyan (a Southeast Barito language). The same features also appear to some degree in Malagasy, a Southeast Barito language in East Africa. The shared linguistic features are the following ones: a grammaticalized form of the originally Malay noun buah ‘fruit’ expressing affectedness, nasal spreading in which N- not only nasalizes the onset of the first syllable but also a *y in the next syllable, a non-volitional marker derived from the Banjar Malay prefix combination ta-pa- (related to Indonesian tər- + pər-), and the change from Proto Malayo-Polynesian *s to h (or Malagasy Ø). These features have their origins in the various members of the language configuration outlined above and form a Sprachbund or “Linguistic Area”. The concept of Linguistic Area is weak and difficult to define. Lyle Campbell (2002) considers it little else than borrowing or diffusion and writes it off as “no more than [a] post hoc attempt [...] to impose geographical order on varied conglomerations of [...] borrowings”. While mindful of its shortcomings, the current author still uses the concept as a useful tool to distinguish betweeninherited and borrowed commonalities. In the configuration of languages currently under discussion it also provides a better understanding of the linguistic situation in South Borneo at a time prior to the Malagasy migrations to East Africa (some thirteen centuries ago).